Translanguaging and Trans-Semiotizing for Critical Integration of Content and Language in Plurilingual Educational Settings - Sohn, Bong-gi; dos Santos, Pedro; Lin, Angel M. Y. (RELC journal, 2022)
Arising in Europe in the early 1990s, content and language integrated learning (CLIL) has become a popular educational approach. CLIL involves a dual focus on content and language learning with an additional language used as the medium of instruction. Although CLIL has received much attention and spread widely around the world, there is limited discussion that critically examines CLIL in relation to its core construct of integration between content and language learning. In particular, the phrasing of ‘content and language integrated learning’ gestures towards viewing language and content as separate entities. With these fundamental issues in mind, we discuss ways in which translanguaging pedagogies can provide a fruitful direction towards a critical integration of content and language learning in multilingual settings. With a view to contributing to a dynamic integration of content and language learning, we argue that CLIL pedagogies informed by translanguaging allow fluidity in meaning-making practices and critically re-examine the construct of language in CLIL. This approach responds to recent calls for more critical approaches to CLIL in order to challenge ‘English-only’/target-language-only pedagogies, ‘native-(English-)speakerism’, and unequal power relations between content and language teachers in many CLIL programs. Implications of this approach to CLIL classrooms in diverse settings are also discussed.